Analysis of the Effectiveness of Policy on Provision of Article 21 Income Tax Incentives borne by the Government during the Covid-19 Pandemic in the KPP Pratama West Bekasi Region 2020 - Iwan Irwansyah; Dwikora Harjo; W. Septa Zahran; Natasya Priscilla Putri (PT FORMOSA CENDEKIA GLOBAL, 2022)
The Covid-19 pandemic has a negative impact on the economic sector and the taxation sector and also has reduced company income that causing many employees to be affected by salary cuts or layoffs. This dire situation inspired the government to grant Article 21 Income Tax borne by the government incentives in order to ease the burden of mandatory taxes and can help restore people's purchasing power. Objective: To analyze the Article 21 Income Tax borne by the government Incentive Policy in the context of handling Covid-19 at West Bekasi Small Tax Office based on an analysis of effectiveness, obstacles faced, and efforts made to overcome obstacles. Methods: This research was descriptive qualitative. The data collection methods were Observation, Documentation, and interviews. Result: The provision of Article 21 Income Tax borne by the government incentive at West Bekasi Small Tax Office is still not effective because there are still many taxpayers who have not taken advantage of this incentive due to lack of information and socialization provided, this is based on achieving goals, integration, and adaptation. The obstacles faced are the lack of comprehensive socialization because there are still many taxpayers who do not have the information about the incentive so many taxpayers do not take advantage of this policy. There is also a lack of awareness of taxpayers in reporting the realization of the use of Article 21 Income Tax borne by the government incentive. The efforts made by West Bekasi Small Tax Office are by conducting comprehensive socialization and maintaining synergy/cooperation between the Tax Office and taxpayers.